2-Arachidonoylglycerol Reduces the Production of Interferon-Gamma in T Lymphocytes from Patients with Systemic Lupus Erythematosus - Luca Navarini; Marta Vomero; Stefano Di Donato; Damiano Currado; Onorina Berardicurti; Annalisa Marino; Pietro Bearzi; Alice Biaggi; Matteo Ferrito; Piero Ruscitti; Marina Fava; Alessandro Leuti; et al. (Biomedicines, 2022)
Background: the endocannabinoid 2-arachidonoylglycerol (2-AG) plays a pivotal role in immune cells regulation. The plasma levels of 2-AG are increased in patients with systemic lupus erythematosus (SLE) and correlate with disease activity. Moreover, in plasmacytoid dendritic cells from SLE patients, 2-AG is able to control the production of type 1 interferon (IFN) through CB2 activation. The aim of this study was to evaluate the potential role of 2-AG on T lymphocytes from SLE patients. Methods: peripheral blood mononuclear cells (PBMCs) from SLE participants and age- and sex-matched healthy donors (HD) were isolated by Ficoll–Hypaque density-gradient centrifugation. The PBMCs were treated with increasing concentrations of 2-AG, and AM251 and AM630 were used to antagonize CB1 and CB2, respectively. Flow cytometry was used to assess the expression of CD3, CD4, CD8, CD25, IFN-ɣ, IL-4, and IL-17A. Results: 2-AG (1 μM) decreased IFN-ɣ expression (p = 0.0005) in the Th1 lymphocytes of SLE patients. 2-AG did not modulate the cytokine expression of any other T lymphocyte population from either SLE or HD. Treatment with both 2-AG and AM630 increased the IFN-ɣ expression in Th1 lymphocytes of SLE patients (p = 0.03). Discussion: 2-AG is able to modulate type 2 IFN production from CD4+ T lymphocytes from SLE patients through CB2 activation.